Biomarkers for Cancer: A Detail Review - Bhole, Ritesh; Bhondave, Pravin; Chikhale, Rupesh; Bonde, Chandrakant; Gurav, Shailendra (Київський національний університет імені Тараса Шевченка, 2023)
When aberrant cells multiply uncontrolled, transcend their normal borders, invade nearby tissues, or spread to other organs, a wide spectrum of illnesses collectively referred to as "cancer" can arise in practically every organ or tissue of the body. The second-leading cause of death globally in 2018, cancer was expected to be responsible for 9.6 million deaths, or one in every six fatalities. A cancer biomarker is a characteristic that can be used to gauge a patient's likelihood of developing cancer or its outcome. Various biomarkers can be used at molecular and cellular level. It is crucial that biomarkers undergo thorough review, including analytical validation, clinical validation, and appraisal of clinical value, prior to being included into normal clinical treatment because of the crucial role they play at all stages of disease. We discuss important steps in the creation of biomarkers in this review, including how to prevent introducing bias and standards to adhere to when presenting the findings of biomarker research.
Keywords: Biomarker; detection; genes; hormones; DNAzyme